Philosophy Of Nationalism In Sri Aurobindo’s Bande Mataram (Journal of Namibian Studies : History Politics Culture, 2023)
Sri Aurobindo is generally known as “Yogi” but beyond this legendary status he was a freedom fighter profound thinker, metaphysician, philosopher, social reformer, visionary and an ardent nationalist. Sri Aurobindo was indeed a versatile genius. Aurobindo is known as Sri Aurobindo in which ‘Sri’ means beauty of divinity. He had the divine qualities which are concerned for his name.  We can consider him as a prophet of nationalism and lover of humanity. Dr. Radhakrishnan described Sri Aurobindo as 'the most accomplished of modern Indian thinkers'. Rabindranath Tagore painted him as the 'Messiah of Indian culture and civilization'.